2015
DOI: 10.1016/j.jhydrol.2015.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Data-model comparison of soil–water δ 18 O at a temperate site in N. Spain with implications for interpreting speleothem δ 18 O

Abstract: Publication informationJournal of Hydrology, Publisher Elsevier Item record/more information http://hdl.handle.net/10197/7200 Publisher's statementThis is the author's version of a work that was accepted for publication in Journal of Hydrology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…It was shown that the MTT estimations in the soil depend on the applied travel time model [ Timbe et al ., ] and also the sampling frequency has an influence on the estimates of MTT [ Timbe et al ., ]. An alternative dynamic model approach is a combination of mixing and piston flow assumptions, which were shown to be able to simulate the temporal variable travel times through a lysimeter [ Lindström and Rodhe , ] or the stable isotope dynamics of mobile water in 0.6 m soil depth [ Comas‐Bru and McDermott , ]. Given the hydroecological feedbacks presented in the previous sections, which influence the water flow and solute transport, lumped convolution approaches that do not consider transient water flow and evapotranspiration losses within the soil profile seem to oversimplify the processes.…”
Section: Processes In the Soilmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that the MTT estimations in the soil depend on the applied travel time model [ Timbe et al ., ] and also the sampling frequency has an influence on the estimates of MTT [ Timbe et al ., ]. An alternative dynamic model approach is a combination of mixing and piston flow assumptions, which were shown to be able to simulate the temporal variable travel times through a lysimeter [ Lindström and Rodhe , ] or the stable isotope dynamics of mobile water in 0.6 m soil depth [ Comas‐Bru and McDermott , ]. Given the hydroecological feedbacks presented in the previous sections, which influence the water flow and solute transport, lumped convolution approaches that do not consider transient water flow and evapotranspiration losses within the soil profile seem to oversimplify the processes.…”
Section: Processes In the Soilmentioning
confidence: 99%
“…Ultimately, the investigation of the evaporation and the accompanied fractionation in the topsoil depends on the method of choice for the pore water stable isotope sampling. Studies using zero tension, suction lysimeters, or wick samplers, which only investigate water in the large pore sizes, reported only little to no fractionation in the top soil [e.g., Landon et al, 2000;Asano et al, 2002;Timbe et al, 2014;Muñoz-Villers and McDonnell, 2012;Kim and Jung, 2014;Geris et al, 2015;Comas-Bru and McDermott, 2015], while other studies using centrifugation [Kudo et al, 2013], cryogenic vacuum extraction [e.g., Brooks et al, 2010;Goldsmith et al, 2012], or the direct equilibration [e.g., Garvelmann et al, 2012;Bertrand et al, 2012] found a fractionation in the upper soil layer. However, recent publications showed that especially the latter two methods are not necessarily comparable [Orlowski et al, 2016b].…”
Section: 1002/2015rg000515mentioning
confidence: 99%
See 2 more Smart Citations
“…Recycling of moisture contributing to Postojna precipitation takes place mostly in central and eastern Europe, where hydrological balance is often positive (e.g., Wriedt and Bouraoui, 2009) and transpiration is enhanced versus precipitation (e.g., Granier et al, 2000;Domínguez-Villar et al, 2018). Soil water in temperate European sites have shown a limited impact of evaporation on the oxygen isotope signature (Comas-Bru and McDermott, 2015;Riechelmann et al, 2017).…”
Section: Moisture Sources Control On 18 O Values Of Precipitationmentioning
confidence: 99%